EKSISTENSI AREA IMIGRASI PADA TEMPAT PEMERIKSAAN IMIGRASI DI INDONESIA - Gusti Ayu Made Widnyani (University of Udayana, 2016)
Area Immigration is an area that is in every Immigration Check Point (TPI) in which the functions of immigration especially related to the people’s traffic inspection which coming in and out of a country and there are a restricted and a sterile area that can only be traversed by parties concerned like the passengers or crew whom will exit or entry Indonesian territory or official and authorized personnel. Arrangements regarding to the area of ??immigration set in Part Five, Article 22 paragraph (1) of Immigration Law determined that: In every Immigration Checkpoints assigned a specific area to immigration inspection is the area of ??immigration. The existence of the immigration area reflects the immigration service quality standards in a country. As an international area marked by yellow line (yellow line), the area of ??immigration has a position that is as important as the sovereignty of a country. Normatively, immigration area which available in each Immigration Check Point is the place and area that was authorized by the Ministry and has a legal status (legal standing) and legitimate in law. So that the existence of the immigration area is a representation of authority and sovereignty. But immigration area is less effective because of the legal instruments governing inadequate and also people have not been aware of law so that there are many violations happens in the immigration area.